Prevalence of Nonfatal Serious Injury Due to Motor Vehicle Accidents Among Malaysian School-Going Adolescents: Findings From the Adolescent Health Survey 2017. (November 2019) - Awaluddin, S Maria; Ahmad, Fazila Haryati; Jeevananthan, Chandrika; Ganapathy, Shubash Shander; Sooryanarayana, Rajini; Mohamad Anuar, Mohamad Fuad; Alias, Nazirah; Saminathan, Thamil Arasu; Mohd Yusoff, Muhammad Fadhli; Rosman, Azriman
Serious injury due to motor vehicle accidents (MVAs) significantly contributes to the adolescents' health status. The objective of this study was to estimate the prevalence of nonfatal injury due to MVAs and its associated factors among Malaysian school-going adolescents. Nationally representative samples were selected via 2-stage stratified cluster sampling. Data was collected using a validated self-administered questionnaire. Logistic regression analysis was conducted to examine the associations between the variables. A total of 1088 out of 27 497 adolescents reported that they had sustained serious injury due to MVAs with a prevalence of 4.1% (95% confidence interval [CI] = 3.7-4.5). Serious injury due to MVAs among adolescents was positively associated with being current cigarette smokers (adjusted odds ratio [aOR] = 2.5; 95% CI = 2.2-2.9), followed by Malay ethnicity (aOR = 2.4; 95% CI = 1.9-3.0), current drug users (aOR = 2.3; 95% CI = 1.9-3.0), boys (aOR = 2.1; 95% CI = 1.8-2.4), Indian ethnicity (aOR = 1.8; 95% CI = 1.2-2.5), and those who were in upper secondary school (aOR = 1.3; 95% CI = 1.2-1.5). Targeted intervention and curbing substance use among boys may reduce the morbidities from MVAs and its resulting complications.